Protective Effect of Grape and Apple Juices against Cadmium Intoxication in the Kidney of Rats - Handan, Bianca Andrade; De Moura, Carolina Foot Gomes; Cardoso, Caroline Margonato; Santamarina, Aline Boveto; Pisani, Luciana Pellegrini; Ribeiro, Daniel Araki (Drug Research, 2020)
Background The objective of this study was to evaluate protective effect of grape and apple juices against toxicity induced by cadmium in the kidney of rats.Methods A total of 20 male-Wistar rats were distributed into four groups (n=5): Control group: animals received an intraperitoneal (i.p.) injection of 0.9% saline solution and after 15 days, 1 mL of water was administered for 15 days, via gavage; Cadmium group: animals received an intraperitoneal injection of cadmium chloride (1.2 mg/kg) and after 15 days, 1 mL of water was administered for 15 days via gavage; Cadmium+Grape Juice: animals received an i.p. injection of cadmium chloride (1.2 mg/kg), and after 15 days, 0.8 mL of grape juice was administered for 15 days, via gavage; Cadmium+Apple Juice: animals received i.p. injection of cadmium chloride (1.2 mg/kg) and after 15 days, 1.0 mL of apple juice was administered for 15 days, via gavage.Results Histopathological analysis revealed severe tubular lesion and necrosis in the group exposed to cadmium, while animals exposed to grape or apple juices showed a significant reduction of tissue injury. 8-OHdG immunoexpression, DNA damage, cytochrome C and catalase gene expressions and Toll like signaling pathway (TLR2, and pIKKα/β) decreased in animals treated with grape juice when compared to cadmium group.Conclusion Taken together, we conclude that grape and apple juices had a protective effect by means of antioxidant, antigenotoxic actions and for promoting tissue regeneration in the kidney of rats following cadmium intoxication.
Keywords: biologics; apoptosis; inflammation